O perfil do gestor de futebol contemporâneo: análise comparativa de 2001 e 2017 - Bezerra, Marcio Ferreira (2018)
Football is the most popular sport in the world and every year it moves billions of dollars into an economy that revolves over several categories, most notably with transactions involving players, ticket sales, sponsors, broadcasting rights and championship awards. Thus, the sport that turned spectacle, demanded much more professionalism and organizational structure to the height of which was invested. In Brazil, after their mainclubs spend years being driven in an amateur fashion, they are undergoing a process of restructuring based on the professionalization of their areas and the investment in technology to improve performance on and off the field. Thus, this research had as main objective to analyze the competences of the profile of the contemporary sports manager, investigating, great clubs of Brazil, through interviews with those responsible for the management of the key areas of football, documentary analysis and previous studies, such as Master's thesis of Rogério Pimenta, held in 2001, which analyzed the profile of sports managers in Brazil. Also as a secondary objective, draw a comparison between the profiles of professionals from 2001 and 2017, analyzing the main similarities and differences. Among the main results, we highlight the investments in information technology that are able to create and share the knowledge produced between the main areas of the club: professional football, grassroots football and performance and market analysis. Thus, the profiles of the managers are characterized by professionals, mainly, who have the capacity to understand technology related to sports, communication, knowledge management, planning, organization, creation of work methodologies and people management.